2011
DOI: 10.2319/081910-488.1
|View full text |Cite
|
Sign up to set email alerts
|

Molar height and dentoalveolar compensation in adult subjects with skeletal open bite

Abstract: Objective: To evaluate the skeletal and dentoalveolar components in adult subjects with skeletal open bite in the presence or absence of dental compensation. Materials and Methods: The study sample included 69 adult female subjects who belonged to three groups according to skeletal vertical relationships and overbite. A total of 15 variables (5 angular, 10 linear) were evaluated. Values in the dentally compensated open bite group (COBG), the dentally noncompensated open bite group (NCOBG), and the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
1
29
1
3
Order By: Relevance
“…This is in agreement with other research, which found that the open bite group did not differ significantly from a CG in this regard. 12,23,24 The ULH was not statistically significantly different between SOBGs and CG. This makes sense as the length of the upper lip is not influenced by the sagittal skeletal malocclusion.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This is in agreement with other research, which found that the open bite group did not differ significantly from a CG in this regard. 12,23,24 The ULH was not statistically significantly different between SOBGs and CG. This makes sense as the length of the upper lip is not influenced by the sagittal skeletal malocclusion.…”
Section: Discussionmentioning
confidence: 85%
“…Burstone et al 17 found that the distance of the upper incisor edge to the PP in males was 30.5 6 2.1 mm and in females 27.5 6 1.7 mm, where larger values were considered as overeruption and smaller values as infraeruption. Also, Kucera et al 12 found that in the skeletal open bite group, the incisor height was significantly elongated compared with CG by approximately 3 mm. Our results were consistent with those of previous studies, [12][13][14][15][16][17][18][19] but they contradict those reported by Nahoum,20 who found smaller values for incisor height in patients with open bite with respect to CG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations